Relating Habitat Suitability and Survival Rates in a Phylogenetic Framework - Eun Hye Kim; James D. Hitchmough; Ross W. Cameron; Volker Bahn; Franziska Schrodt (Ecology and Evolution)
ABSTRACT Species distribution models rely on species' observed geographic distributions, which reflect only subset of the true ecological niche. This inevitably leads to discrepancies between the predictions of habitat suitability (HS) and the actual ecological performance in novel environments beyond the trained range. We examined this limitation by comparing modelled HS with empirical survival rates (SRs) of three Acer species, A. davidii, A. palmatum, and A. pictum, cultivated in the UK botanic gardens. We hypothesise that ex‐situ species with greater niche overlap with native UK/European species will show higher HS, which also correspond to species' SR relative to that of local species. This HS‐SR alignment will then indicate the alignment of species' geographic range and ecological range. We first quantified niche similarity between these East Asian species and UK/Europe native Acer species at both regional and continental scales. MaxEnt models were calibrated using native occurrences with various combinations of environmental variables and model configurations, then projected onto UK regions. Species' SRs were standardised against those of native species using long‐term inventory data. Our results show that niche overlap with native species generally corresponded to predicted HS, while observed SR patterns revealed an inverse relationship. A. davidii, showing high niche overlap and high HS, exhibited the lowest SR. Contrarily, A. pictum, despite showing low niche overlap and predicting most regions unsuitable, demonstrated the highest SR, comparable to native species. This discrepancy was particularly noteworthy as A. pictum shared closer phylogenetic relationships with European species, while A. davidii was more closely related to North American species. The observed phylogenetic signal in SR patterns suggests that intrinsic traits that relate to climate tolerance may be conserved yet masked in the conventional modelling approach. This interdisciplinary approach bridges the gap between macro‐scale predictions and local‐scale individual performance, offering a new perspective on niche conservatism through a phylogenetic framework.